Can music influence cardiac autonomic system? A systematic review and narrative synthesis to evaluate its impact on heart rate variability - Mojtabavi, Helia (2020)
Background: and purpose: The impact of music on the human body extends beyond an emotional response. Music can bring benefits to the cardiovascular system by influencing heart rate variability (HRV), which is a well-accepted method to analyze the oscillations of the intervals between successive heartbeats and investigate the cardiovascular autonomic nervous system (ANS). This study is a systematic review to examine the effect of musical interventions on HRV. Methods: We conducted a systematic search in PubMed, Scopus, Web of Science, and Cochrane and identified additional studies with hand searching of reference lists of relevant references. Results: 29 original articles (24 pre-post intervention studies and five randomized controlled trials) with a total of 1368 subjects were available and eligible to be included in the systematic review. Within the whole, only three studies reveal no significant impact of music on HRV, which might be due to using a small sample size and a concise duration of music administration. Interestingly, the rest of the studies have suggested a positive impact of music on HRV with a 0.05 level of significance. Conclusion: This systematic review confirms music as a stimulus acting to the cardiac ANS that increases parasympathetic activity and HRV. The effects are, however, associated with a high risk of bias. Therefore, further studies are necessary to compare the impact of individualized music therapy to passive listening and preferred soundtracks.